If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3z + -1 = 26 Reorder the terms: -1 + 3z = 26 Solving -1 + 3z = 26 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 3z = 26 + 1 Combine like terms: -1 + 1 = 0 0 + 3z = 26 + 1 3z = 26 + 1 Combine like terms: 26 + 1 = 27 3z = 27 Divide each side by '3'. z = 9 Simplifying z = 9
| 7(6-x)=63 | | -6(1-5y)=54 | | k*9-3=-11 | | 25x-3=6(3x-2)+7x+9 | | -s+2=-3s-6 | | 9-1g=2g | | x=1.5+.75*-2 | | m*7-9=5 | | 2g+3=9 | | 2p+38=5p+5 | | 4x-16=2x-4 | | 7x-2=1-12x | | 4+n*5=29 | | M+8=9 | | x=1.5+.75*-3 | | p=b+4a+c | | 6(-1x-2)=6 | | 3n+0=3n | | 3x^2+72=33x | | 5-4(a+2)=7+a | | 8x-5x-x=21 | | x=1.5+.75*3 | | 4u-4=-10u+24 | | s^2+16=8s | | 20x-10=40 | | 9x^2+42x=-49 | | 8x-3x-x=21 | | -8-5d+9d+6=0 | | -9x=3 | | (-10-7i)-(5-3i)= | | 8x+7=2x+9 | | 4p-3=2+p |